2012
DOI: 10.1057/ejis.2011.47
|View full text |Cite
|
Sign up to set email alerts
|

Escaping ‘localisms’ in IT sourcing: tracing changes in institutional logics in an Italian firm

Abstract: Organizations are limited in their choices by the institutional environment in which they operate. This is particularly true for IT sourcing decisions that go beyond cost considerations and are constrained by traditions, geographical location, and social networks. This article investigates how a company can disentangle itself from the constraints of the institutional environment. We do so drawing on a longitudinal case study of an Italian SME active in the steel industry that successfully changed its instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…• Reviewability (Faraj et al, 2011) • Persistence • Metavoicing (Majchrzak et al, 2013) • Conceptual • Conceptual • Conceptual While the affordances help us to understand the potential role of technology for knowledge sharing, studies on affordances do not take into account the wider institutional context that influences users' interaction with a technology. In line with the growing body of research on institutional theory and IS (Ang & Cummings, 1997;Berente & Yoo, 2011;Currie & Guah, 2007;Mola & Carugati, 2011;Seidel & Berente, 2013), we take the position that particular uses of a technology are influenced by institutional forces applicable across various contexts. In order to fully understand users' knowledge sharing practices on ESM, it is essential to include an institutional logics perspective as it allows us to explain how affordances are engaged in practice.…”
Section: Persistencementioning
confidence: 99%
“…• Reviewability (Faraj et al, 2011) • Persistence • Metavoicing (Majchrzak et al, 2013) • Conceptual • Conceptual • Conceptual While the affordances help us to understand the potential role of technology for knowledge sharing, studies on affordances do not take into account the wider institutional context that influences users' interaction with a technology. In line with the growing body of research on institutional theory and IS (Ang & Cummings, 1997;Berente & Yoo, 2011;Currie & Guah, 2007;Mola & Carugati, 2011;Seidel & Berente, 2013), we take the position that particular uses of a technology are influenced by institutional forces applicable across various contexts. In order to fully understand users' knowledge sharing practices on ESM, it is essential to include an institutional logics perspective as it allows us to explain how affordances are engaged in practice.…”
Section: Persistencementioning
confidence: 99%
“…Building on this boundary‐spanning role in the investigated institutional context, the contrast between the current and desired states was important and multifaceted prompting a misalignment of interests (Mola & Carugati, ). The misalignment was a consequence of both the technological change and the very engine of the change effort, namely a natural state of affairs in complex organisations with multiple, coexisting interests (Battilana & Dorado, ).…”
Section: Discussionmentioning
confidence: 99%
“…With a few exceptions (Mola & Carugati, 2012), most research in Information Systems (IS) shows how tension between logics persists across time (eg, Hayes & Rajao, 2011), which plunges IT-enabled transformations in a precarious equilibrium that is continually contested and renegotiated. For example, as an attempt to compromise between conflicting logics, a new technology can be readapted to conform to the practices and norms of the implementation context (Carugati, Fernández, Mola, & Rossignoli, 2018;Davidson & Chismar, 2007).…”
Section: Institutional Logics and It Innovationmentioning
confidence: 99%
“…An example is guidelines of clinical safety established by knowledge elites (eg, NICE) as a complex form of discipline and "self-surveillance" (Waring, 2014) and used by clinical managers to evaluate an IT innovation. The interpretation of evidence is both contextual and contested (Fitzgerald, Ferlie, & Hawkins, 2003) due to the role of institutional logics in filtering actors' perceptions about the risk and effectiveness of IT investments (Mola & Carugati, 2012). The case study showed that from the point of view of a medical professional, the apparent lack of evidence of clinical effectiveness and, most of all, clinical safety is strongly related to workload concerns and the integrity of medical practice.…”
Section: F I G U R E 1 the Role Of Hybrids In Managing Competing Instmentioning
confidence: 99%
See 1 more Smart Citation